An Assessment of Candidal Colonization and Species Differentiation in Head and Neck Cancer Patients Receiving Radiation - Shrestha, M; Boaz, K; Srikant, N; Shakya, A (Journal of Nepal Health Research Council, 2015)
Background: Oral colonization with Candida species has been observed in upto 93% of patients receiving radiation for head and neck cancer. With immunosuppression there is a trend of emergence of rare species. The present study aimed to assess species and colonization of candida at different stages of radiation therapy for head and neck cancer.Methods: Oral rinses of thirty cancer patients receiving a six weeks course of radiation therapy for head and neck cancer were taken at two intervals; first at the start of radiation (0 Grays), and second at completion of radiation(60 Grays). The oral rinse was streaked onto a differential media (CHROMagar) plates and incubated at 37ÂºC for 48 hours. Colony forming units (CFU) were counted and species were differentiated. Fifteen healthy controls werecompared.Â Results: The candida albicans colony count (CFU/ml) at baseline, 0 Grays radiation ranged from 50 to 1820 CFU/ml in cases and from 0 to 300 CFU/ml in controls. C. albicans was seen in all cases (100%) and most of the controls(86.66%). Other species such as C. Krusei, C. parapsilosis, C .tropicalis, and C. glabrata were observed with a frequency of 10%, 6.66%, 3.33%, and 3.33% respectively in the cases. However, no species other than C. albicans was observed in controls.Conclusions: Immunosupression of radiation therapy patients led to the development of species other than Candida albicans, which is the most prevalent species. Thus it can be inferred that there is emergence of the opportunisticfungal pathogens in patients with immunosupression.Keywords: candidal colonization; CHROMagar@ ; differential media; immunosupression